Sebuah Perancangan Brand Identity Industri Kecil Menengah “Pawone Unin” sebagai Identitas Usaha Katering di kota Malang - Mifthahul Haeruddin Wijaya; Pujiyanto Pujiyanto; Mahendra Wibawa (MAVIS : Jurnal Desain Komunikasi Visual, 2020)
Small and Medium Industry Pawone Unin is a catering business in the city of Malang which was founded in 2015 to offer products and services but does not yet have a business identity to be recognized by the wider community, so it is necessary to design a Small and Medium Industry Brand Identity "Pawone Unin" as a Catering Business Identity in the Malang City. The design of the brand identity is carried out through the stages of data collection such as observation, interviews, questionnaires, document data and library data, then the design method uses the brainstorming, thumbnail, rough sketch, and comprehensive stages. Designing Small and Medium Industry Brand Identity "Pawone Unin" as Catering Business Identity In Malang City produces an identity in the form of a logo and a logo application guidebook as the main media and supporting media in the form of business equipment and promotional media. The conclusion is that the Design of Small and Medium Industry Brand Identity "Pawone Unin" as a Catering Business Identity in Malang City produces design results in the form of brand identity, graphic standard manuals or application manuals, and implementation media.